A New Species of Diploderma Hallowell, 1861 (Reptilia, Squamata, Agamidae) from Northeastern Yunnan Province, China - Shuo Liu; Mian Hou; Dingqi Rao (Taxonomy, 2024)
A new species of the genus Diploderma Hallowell, 1861 from Qiaojia County, Zhaotong City, northeastern Yunnan Province, China, is described. Phylogenetically, the new species is placed within the D. splendidum complex and has genetic distances of 7.3% and 7.5% from D. splendidum (Barbour & Dunn, 1919) sensu stricto and D. daduense Cai, Liu & Chang, 2024, respectively, based on the ND2 gene sequences. Morphologically, the new species closely resembles D. splendidum sensu stricto and D. daduense, however, it can be distinguished from D. splendidum sensu stricto by having a larger body size in males and relatively shorter limbs, and can be differentiated from D. daduense by having a relatively narrower head in males and relatively shorter forelimbs in males. In addition, the new species differs from D. splendidum sensu stricto and D. daduense by having different colorations, especially in the absence of transverse stripes on the dorsal head. This study further revealed that D. splendidum sensu lato is a complex containing multiple species and that more research is needed to clarify the taxonomy of the complex.